Using Virtual Reality and Augmented Reality to Learning Mathematics - Julia Nurlita; Salwa Sabria Ramadhani; Wahyunengsih Wahyunengsih (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
The purpose of this study was to develop and test a mathematics learning tool using Virtual Reality (VR) technology on the Android platform. The material focused on is flat-sided spatial objects for junior high school students. The development stages were carried out through various steps, from planning to testing on students. The findings showed that the media was considered appropriate by experts, easily accessible to students, and contributed to improving learning outcomes. In addition, students appeared more enthusiastic and excited during the learning process. A review of two other articles confirmed that VR and AR-based media were able to improve understanding and make learning more enjoyable. This tool could be an interesting alternative for teaching mathematics.